Synergism of Tephrosia vogelii and Piper aduncum Based Nanoemulation Against Spodoptera frugiperda - Sang Phước Nguyễn; Eka Candra Lina; Hidrayani Hidrayani; Munzir Busniah (International Journal of Agricultural Sciences, 2022)
The botanical insecticide nanoemulsion is a pesticide having an oil phase and aqueous phase that spontaneously emulsify and range in size from 20 to 200 nm. Bio-combi extracts frequently contain intricate combinations of active ingredients that may work in concert to increase bioactivity. The goal of the study was to develop the optimal nanoformulation and investigate the physiological effects of a synergistic nanoemulsion made from Tephrosia vogelii leaves and Piper aduncum fruit extracts as a substitute pesticide for Spodoptera frugiperda larvae. Low-energy spontaneous emulsification with a magnetic stirrer was used to create nanoemulsions, which were then subjected to a toxicity and food absorption test. Malvern's Zetasizer Nano (ZN), which was used to analyze the insecticidal nano formulae for PSA, revealed that the particle sizes for the 1:1, 3:1, and 1:5 ratios were 204 nm, 4724 nm, and 97 nm, respectively. Only the 1:5 formula, which is classified as a nanoparticle, met the standards for a nanoemulsion and produced S. frugiperda mortality of 82.34% at a concentration of 0.56%, and the LC25, LC50, and LC95 values were 0.1, 0.22, and 1.59%, respectively. The analyzable results demonstrated that the mixed nanoemulsion was additive at the LC50 value was 0.95 while the LC95 value was 0.70%, meaning only marginally synergistic